Impact of the COVID-19 Pandemic on Survival in the Patients With the Intra-Abdominal Infections - Gálvez-Benítez, Lydia; Rodríguez-Villodres, Ángel; Álvarez-Marín, Rocío; Jiménez-Rodríguez, Rosa; Lepe-Jiménez, José Antonio; Pachón, Jerónimo; Smani, Younes (Frontiers in Medicine, 2021)
Objective: To analyze the availability and access to the hospital for the patients with intra-abdominal infections (IAIs) by Escherichia coli (E. coli) as a result of the coronavirus disease 2019 (COVID-19) pandemic and the impact of these changes in the diagnosis and their effects on the death of these patients. Methods: Two prospective observational cohorts of the patients with IAI by E. coli were conducted in 2016 (the pre-COVID-19, n = 108) and in 2020 (during the COVID-19, n = 96) at the University Hospital of Seville, Spain. The demographic and clinical variables of the patients were collected and analyzed. The patients were followed-up for 120 days, until the hospital discharge or death. The bivariate and multivariate analyses were performed. Results: Both the cohorts were homogeneous according to age, sex, emergency surgery cause, immunosuppression, neutropenia, acquisition type, and previous intervention. The patients attended during the COVID-19 had significantly higher Charlson comorbidity index and the more McCabe score, required more emergency surgery, had more severe infections with the higher rates of septic shock and sepsis, and the presence of additional care support such as a nasogastric tube. They were diagnosed later; the time intervals between the symptoms onset (SO) to the first medical contact or surgical intervention (SI) and between the first medical contact to the admission or SI were significantly higher. The death rates during the COVID-19 and the pre-COVID-19 were 16.7 and 6.5%, respectively (p = 0.02). Finally, the multivariate analysis in both the cohorts together identified the patients diagnosed during the COVID-19, the longer period from SO to SI, septic shock, and the Charlson comorbidity index as the independent factors associated with death. Conclusion: This study showed the impact of the COVID-19 pandemic on the clinical outcome and death due to IAI with an extension of the time between SO and SI.